Nutritional and biotechnological potential of SCOBY produced in green tea fermentation (Research, Society and Development, 2022)
Kombucha is an ancient beverage with claims of functional properties that has become popular in Brazil, resulting from the fermentation of green and/or black tea by a symbiotic association of bacteria and yeast, SCOBY (Symbiotic Culture Of Bacteria and Yeast). It aims to carry out an integrative review of the literature to describe the main biological attributes of Kombucha, in order to demonstrate the health benefits, in the current perspective of the market and its biotechnological potential. Kombucha is a fermented tea-based drink of Asian origin, produced by a technique of fermenting sweetened black or green tea, promoted by a culture of yeast and bacteria. The chemical composition is variable both quantitatively and qualitatively, as it depends on the fermentation and substrates used in the initial tea, being related to the ingredients used in its manufacture and the processes applied. Its frequent consumption has benefits related to its antioxidant activity with potential ability to scavenge free radicals, and with that attracting the interest of the global market, in 2019, the kombucha industry was worth US$ 1.67 billion and is expected to grow more and more. Therefore, the use of SCOBY as a way of obtaining bacterial cellulose becomes an alternative with potential for profitability, in the characterization of the proximate composition of SCOBY, it is found levels of protein and dietary fiber in its proximate composition, in order to constitute a alternative source of human food.